Current Directions Ensuring the Safety of Tourists in the Republic of Uzbekistan - O. Sh., Aminov (European Journal of Life Safety and Stability (2660-9630), 2023)
Ensuring the safety of tourists is one of the main directions in the program to improve tourism should have a legal, economic, financial, organizational, informational and personnel basis. First of all, a clear definition of the goal is necessary. From the very beginning it should be clear what socio-economic problem must be solved, what parameters must be achieved.